Statistical model for assessing the resilience of the public supply chain and its influence on regional project management in Peru - Talenas Quispe, Raul Walther (2025)
Public infrastructure projects in Peru face structural challenges in supply chain management, resulting in delays, cost overruns, and quality deficiencies. This study examined the extent to which supply chain resilience influences project effectiveness regarding time, cost, and quality standards. A quantitative, correlational–explanatory, non-experimental design was adopted, using surveys administered to professionals engaged in public works management. Statistical analysis included Pearson correlation, linear regression, Chi-square, ANOVA, and logistic regression. Results showed a strong and significant relationship between resilience and effectiveness (r = 0.782; p < 0.05), with resilience explaining 61.1% of performance variability. Critical deficiencies were identified in administrative coordination, reliance on external suppliers, and insufficient quality control. Conversely, implementing the Deming Cycle (PDCA) and PMBOK practices had a positive effect, accounting for 50.5% of the improvement in resilience and effectiveness. The findings conclude that resilience is a structural determinant of public project success, and strengthening it through supplier diversification, effective coordination, and systematic quality control is essential to ensure the sustainability of infrastructure investments.